The Influence of Transformational Leadership Style, Work Environment and Workload on Organizational Commitment - Dewi Masithoh; Raden Ayu Aminah Rizkia Puspita Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research explores how transformational leadership, work environment, and workload affect the organizational commitment of the Kebumen Regency Education, Youth, and Sports Office. This census-based quantitative study used a sample of 120 respondents, and data were collected through questionnaires. Validity, reliability, and classical assumptions were tested before the analysis. Multiple linear regression analysis was conducted using SPSS 26 to test the relationships between variables. The findings reveal that transformational leadership does not have a significant effect on organizational commitment. On the other hand, an excellent work environment greatly enhances employee welfare and has a substantial positive impact on organizational commitment. Workload is also found to positively affect organizational commitment, as a proportional workload encourages higher levels of employee accountability. Together, these three independent variables explain 55.4% of the variance in organizational commitment, with other factors accounting for the remaining portion. The study concludes that improving the work environment and managing workload effectively are key factors in increasing organizational commitment.